2019
DOI: 10.1002/lary.28211
|View full text |Cite
|
Sign up to set email alerts
|

Voice‐Related Quality of Life Increases With a Talking Tracheostomy Tube: A Randomized Controlled Trial

Abstract: Objective: The primary objective of our study was to determine the quality of life (QOL) using a talking tracheostomy tube. Methods: Randomized clinical trial (NCT2018562). Adult intensive care unit patients who were mechanically ventilated, awake, alert, attempting to communicate, English-speaking, and could not tolerate one-way speaking valve were included. Intervention comprised a Blue Line Ultra Suctionaid (BLUSA) talking tracheostomy tube (Smiths Medical, Dublin, OH, US). Outcome measures included QOL sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“… 59 One randomised controlled trial used talk tubes and found significant improvements in voice-related quality of life. 53 Another used in-line speaking valves and favoured the use of in-line valves over one-way speaking valve but found that the improvement in quality of life was not statistically significant. 44 …”
Section: Resultsmentioning
confidence: 99%
“… 59 One randomised controlled trial used talk tubes and found significant improvements in voice-related quality of life. 53 Another used in-line speaking valves and favoured the use of in-line valves over one-way speaking valve but found that the improvement in quality of life was not statistically significant. 44 …”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][12][13][14][15][16][17][18][19]21,22,24 Furthermore, ACV could improve V-RQOL and QOL-MV. 23 Several minor complications (eg, discomfort, excessive secretion, cuff breakage) were described. 7,8,[14][15][16][17]19,24 Moreover, two serious adverse events (ie, tracheal distention and subcutaneous emphysema) resulted from the incorrect application of the method and incorrectly placed tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs including 75 patients reported V-RQOL and QOL-MV. 20,23 In the first pilot RCT there were no significant differences between the intervention (n = 15) and control groups (n = 10). 20 The overall quality of evidence for the effect on QOL according to GRADE was very low (Table 2).…”
Section: Quality Of Lifementioning
confidence: 95%
See 1 more Smart Citation
“…127 Patients benefit from reductions in anxiety, shorter times to vocalisation, and earlier oral intake after tracheostomy. 127,149,150 The ability to track these metrics over time and benchmark between sites will add rigor to comparisons as the database expands. The UK Improving Tracheostomy Care project, reported in this issue, details not just the potential quality, safety, and economic impact, but also affords powerful insights into strategies for changes that are likely reproducible in sites around the world.…”
Section: Discussionmentioning
confidence: 99%